Virtual Laboratory for Power Electronic Based Reactive Power Compensators - Coteli, Resul; Gokcan, Ali Osman (Univ Osijek, Tech Fac, 2018)
The practical application is important in engineering education. However, in some cases, such as fund deficiency, practical applications may not be possible. In addition, this case restricts closely to pursue the novel technologies. Depending on developments in power electronics and microprocessor fields, use of Flexible Alternating Current Transmission Systems (FACTS) devices have been becoming more common. Practical applications on these devices are insufficient in undergraduate education. This study presents a virtual laboratory application for power electronics based FACTS devices. The virtual laboratory for education of advanced compensation method is prepared by using MATLAB GUI. The all parameters belonging to the related circuit can be accessed via the prepared virtual laboratory. Over a visual interface, current, voltage and power values can be observed. Theoretical information about the related subject is also included in the prepared virtual laboratory. All possible applications can be done even if users do not know MATLAB Programming Language, GUI, any formula or command from Simulink. User can repeat the application as much as they want and observe results obtained from different parameter values.
Keywords: FACTS devices; power electronics based reactive power compensators; reactive power compensation; virtual laboratory